2004
DOI: 10.4314/ajpherd.v9i3.24646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8 weeks resistance training on serum lipids in sedentary male smokers

Abstract: SummaryEpidemiological studies have found plasma lipid and lipoprotein levels to be predictive of cardiovascular disease in adults. To date, regular aerobic modes of exercise have been associated with favourable alterations in lipid and lipoprotein levels. However, the effect of resistance training on lipid and lipoprotein levels is inconclusive and conflicting. Therefore, the aim of this study was to provide some clarity on whether resistance training could be used to improve sedentary male smokers’ lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
0
13
1
2
Order By: Relevance
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…While some authors claim that the lipid profile of athletes engaging in anaerobic activities is similar to that seen in those who perform aerobic activities, others have reported no change or even a worsening profile. [144][145][146] It can be concluded that at the moment there are not enough data to claim that anaerobic activity exerts any favourable effects on the lipoprotein pattern.…”
Section: Physical Activity and Exercise In Normolipidaemic Subjectsmentioning
confidence: 99%
“…Os grupos TC, juntamente com o TF, demonstraram diminuição do colesterol LDL corroborando, assim, com outros achados da literatura (31,32). Por outro lado, alguns estudos não têm demonstrado alterações com o TF (33). Sugere-se que alterações no colesterol LDL com TF ocorram somente quando este é realizado com intensidades acima de 70% de 1-RM, por períodos maiores que 12 semanas (34).…”
Section: Consumo De Oxigênio Pico (Vo 2pico )unclassified